(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Plasticulture is a method of producing crops in which the use of plastic polymers provides a major advantage. Plasticulture arose from of the late 1930s research and innovation of polyethylene polymer, which was later commercialized as plastic films, mulches, as well as drip-irrigation tubes but also tape in the early 1950s. Other polymers, like as polyvinyl chloride, polypropylene, as well as polyesters, were subsequently developed and used in pipes, fittings, fertilizer application equipment, connectors, including row coverings, extending the usage of plastic elements in this industrial system even further. Plastic mulches, fertigation/chemigation, drip irrigation, fumigation, solarization, windbreaks, stand creating technology, seasonal-extending technology, pest controls, cropping methods, postharvest handling, and marketing are all part of the plasticulture system.. Plasticulture-based vegetable crops production is undeniably a labor-intensive process with high input costs and management needs.